PATOGENICIDADE DE Bacillus thuringiensis VAR. kurstaki (H:3ª-3b) PARA O CURUQUERÊ DO ALGODÃO, Alabama argillacea (HUBNER, 1818) (LEPIDOPTERA, NOCTUIDAE) - Habib, Mohamed E. M.; Andrade, Carlos F. S. de (REVISTA DE AGRICULTURA, 2015)
PATOGENICIDADE DE Bacillus thuringiensis VAR. kurstaki (H:3ª-3b) PARA O CURUQUERÊ DO ALGODÃO, Alabama argillacea (HUBNER, 1818) (LEPIDOPTERA, NOCTUIDAE)